2018
DOI: 10.1088/1873-7005/aa9d77
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of spiral instabilities in wide-gap spherical Couette flow

Abstract: spiral waves of wavenumber m = 5, 4 and 3 are in good agreement with previous experimental results. The present transition scenario of the spiral wavenumber with increasing Reynolds number for 0.33 b = is the same as that of Egbers and Rath (1995 Acta Mech. 111 125-40), while for 0.50 b = , it is only partially similar to those of Wulf et al (1999 Phys. Fluids 11 1359 and Egbers and Rath (1995 Acta Mech. 111 125-40).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…It was confirmed that some of these values align remarkably well with theoretical predictions based on linear stability analysis [12][13][14]. A recent investigation with a further increase in the Reynolds number suggested relaminarization, non-uniqueness, and hysteresis in successive transition processes in an SCF [15][16][17][18]. These aspects in a wide-gap SCF can be regarded as a type of competition among different polygonal structures, which plays an important role in the route to turbulence.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…It was confirmed that some of these values align remarkably well with theoretical predictions based on linear stability analysis [12][13][14]. A recent investigation with a further increase in the Reynolds number suggested relaminarization, non-uniqueness, and hysteresis in successive transition processes in an SCF [15][16][17][18]. These aspects in a wide-gap SCF can be regarded as a type of competition among different polygonal structures, which plays an important role in the route to turbulence.…”
Section: Introductionsupporting
confidence: 77%
“…[9] at η = 1/2 and Ref. [15,18] at η = 2/3), and they are located at the values (η, Ra) where the state was obtained experimentally or numerically. cases and found that the transition was initiated by the axisymmetric Taylor vortices with successive instability where η > 3/4, as observed in the cylindrical Taylor-Couette flow [15].…”
Section: Resultsmentioning
confidence: 87%
“…This is associated with the non-uniqueness of the equilibrium states realisable via hysteresis over Re cr , as reported in Ref. [5], which have been investigated in detail numerically [25]. Hereafter, we refer to the non-axisymmetric equilibrium state with m spiral arms from a pole as an "m-fold spiral state".…”
Section: Resultsmentioning
confidence: 75%
“…At a certain critical Re c nonaxisymmetric instabilities give rise to regular flows whose pattern and topology depend strongly on the gap width χ = r i /r o (with r i and r o being the inner and outer radii) of the problem. When the shell is thin, Taylor-Görtler vortices develop [20][21][22] contrasting with the spiral waves [23][24][25] preferred at wider gaps. In the latter case, triadic resonances were found in a recent study (see Ref.…”
Section: Introductionmentioning
confidence: 99%